2009
DOI: 10.1186/1471-2121-10-84
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant trafficking of NSCLC-associated EGFR mutants through the endocytic recycling pathway promotes interaction with Src@

Abstract: BackgroundEpidermal growth factor receptor (EGFR) controls a wide range of cellular processes, and altered EGFR signaling contributes to human cancer. EGFR kinase domain mutants found in non-small cell lung cancer (NSCLC) are constitutively active, a trait critical for cell transformation through activation of downstream pathways. Endocytic trafficking of EGFR is a major regulatory mechanism as ligand-induced lysosomal degradation results in termination of signaling. While numerous studies have examined mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 72 publications
7
95
0
Order By: Relevance
“…This is the first examination of the relationship between SPRY2 and EGFR expression on EGFR recycling in NSCLC cells. Although it was previously reported that mutant EGFR colocalized with transferrin (Chung et al, 2009), suggesting that mutant EGFR is preferentially recycled, our measurements are the first quantitative comparison of recycling between wild-type and mutant EGFR, as far as we are aware. We found that mutant EGFR was almost entirely sorted for recycling (f r .0.9), whereas wild-type EGFR was split more evenly between degradation and recycling (f r ,0.5).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This is the first examination of the relationship between SPRY2 and EGFR expression on EGFR recycling in NSCLC cells. Although it was previously reported that mutant EGFR colocalized with transferrin (Chung et al, 2009), suggesting that mutant EGFR is preferentially recycled, our measurements are the first quantitative comparison of recycling between wild-type and mutant EGFR, as far as we are aware. We found that mutant EGFR was almost entirely sorted for recycling (f r .0.9), whereas wild-type EGFR was split more evenly between degradation and recycling (f r ,0.5).…”
Section: Discussionmentioning
confidence: 80%
“…6B). It has been suggested previously, based on receptor localization, that mutant EGFR is preferentially recycled (Chung et al, 2009). However, enhanced recycling of mutant EGFR has never been quantified, as far as we are aware.…”
Section: Spry2 Controls Egfr Sorting In An Egfr-expressiondependent Mmentioning
confidence: 99%
“…While we investigated one EGFR phosphorylation site, other sites, such as Tyr 845 , may be involved in the EGFR-Src interaction (16). Interestingly, the interaction of mutated EGFR in cancer with Src is different from the interaction of normal EGFR with Src (14), which may account for the longer time required for Src activation in our EGFR-mutant cell line (Fig. 3).…”
Section: Discussionmentioning
confidence: 98%
“…We have shown that c-Src interacts with oncogenic EGFR mutants in non-small cell lung cancer cells in the ERC, an interaction required for mutant EGFR-mediated oncogenic transformation (112,113). Src has been shown to be a component of the pericentrion (67), suggesting that ErbB2 may signal in collaboration with Src in the ERC.…”
Section: Discussionmentioning
confidence: 99%